2021
DOI: 10.1002/glia.23990
|View full text |Cite
|
Sign up to set email alerts
|

Lamina‐specific properties of spinal astrocytes

Abstract: Astrocytes are indispensable for proper neuronal functioning. Given the diverse needs of neuronal circuits and the variety of tasks astrocytes perform, the perceived homogeneous nature of astrocytes has been questioned. In the spinal dorsal horn, complex neuronal circuitries regulate the integration of sensory information of different modalities. The dorsal horn is organized in a distinct laminar manner based on termination patterns of high‐ and low‐threshold afferent fibers and neuronal properties. Neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 85 publications
(100 reference statements)
1
20
0
2
Order By: Relevance
“…• Transporter expression (e.g., GLAST) • Ion channel expression (e.g., Kir4.1) • Gap junctional coupling (e.g., Cx43) • Ca 2+ signaling (e.g., hippocampus vs. striatum) • Metabolism • Structural properties (e.g., GFAP expression, spine coverage) Chai et al, 2017;Fernández-Moncada et al, 2021;Herde et al, 2020;Hirrlinger et al, 2008;Kelley et al, 2018;Köhler et al, 2021;Köhler et al, 2018;Kronschläger et al, 2021;Miller et al, 2019;Oheim et al, 2018;Olsen et al, 2007 used to study primate-specific interlaminar astrocytes in mice (Padmashri et al, 2021). Strikingly, grafting human astrocytes into the mouse forebrain enhanced synaptic plasticity and learning (Han et al, 2013).…”
Section: Computational Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…• Transporter expression (e.g., GLAST) • Ion channel expression (e.g., Kir4.1) • Gap junctional coupling (e.g., Cx43) • Ca 2+ signaling (e.g., hippocampus vs. striatum) • Metabolism • Structural properties (e.g., GFAP expression, spine coverage) Chai et al, 2017;Fernández-Moncada et al, 2021;Herde et al, 2020;Hirrlinger et al, 2008;Kelley et al, 2018;Köhler et al, 2021;Köhler et al, 2018;Kronschläger et al, 2021;Miller et al, 2019;Oheim et al, 2018;Olsen et al, 2007 used to study primate-specific interlaminar astrocytes in mice (Padmashri et al, 2021). Strikingly, grafting human astrocytes into the mouse forebrain enhanced synaptic plasticity and learning (Han et al, 2013).…”
Section: Computational Analysismentioning
confidence: 99%
“…Chai et al, 2017; Fernández‐Moncada et al, 2021; Herde et al, 2020; Hirrlinger et al, 2008; Kelley et al, 2018; Köhler et al, 2021; Köhler et al, 2018; Kronschläger et al, 2021; Miller et al, 2019; Oheim et al, 2018; Olsen et al, 2007; Theis & Giaume, 2012…”
Section: Challenges In Interpreting Astrocyte Functionunclassified
See 1 more Smart Citation
“…In addition to distinct interactions with neurons, spinal cord astrocytes also exhibit unique physiological properties. A recent study demonstrated that while astrocytes in lamina I have faster coupling speed, higher responsiveness to potassium channel blockage and higher expression of AQP4 than astrocytes in lamina III, their basal membrane properties are similar (Kronschläger et al, 2021). This prompted us to compare passive conductance, I-V curve, and resting membrane potential between Lfng-GFP 1 and ventral Lfng-GFPastrocytes, where we found no differences between these populations.…”
Section: Discussionmentioning
confidence: 73%
“…Synaptic inputs from peripheral sensory neurons into the CNS occur in the dorsal horn of the spinal cord, which is densely populated by astrocytes. Recent studies found that dorsal astrocytes exhibit unique patterns of marker gene expression and laminar-specific coupling speed (Kronschläger et al, 2021). Accordingly, astrocytes have been implicated in sensory processing, where the inhibition of astrocyte proliferation reduced injury-induced tactile allodynia (Tsuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%